Phase-Field Models for Multi-Component Fluid Flows (Communications in Computational Physics, 2012)
In this paper, we review the recent development of phase-field models andtheir numerical methods for multi-component fluid flows with interfacial phenomena. The models consist of a Navier-Stokes system coupled with a multi-componentCahn-Hilliard system through a phase-field dependent surface tension force, variabledensity and viscosity, and the advection term. The classical infinitely thin boundary ofseparation between two immiscible fluids is replaced by a transition region of a smallbut finite width, across which the composition of the mixture changes continuously. Aconstant level set of the phase-field is used to capture the interface between two immiscible fluids. Phase-field methods are capable of computing topological changes suchas splitting and merging, and thus have been applied successfully to multi-componentfluid flows involving large interface deformations. Practical applications are providedto illustrate the usefulness of using a phase-field method. Computational results ofvarious experiments show the accuracy and effectiveness of phase-field models.